A retrospective, single-centre safety audit of the Altis® single incision sling in the surgical treatment of female stress urinary incontinence - E. Collier; S. Housmans; F. Van der Aa (Continence)
Background:: Single incision slings (SIS) and adjustable single incision slings (ASIS) are the latest generation of midurethral slings (MUS), used for the surgical treatment of female stress urinary incontinence, that seek to minimize the morbidity and complications associated to the conventional retropubic and transobturator midurethral slings. Its use has recently come under scrutiny following concerns about long-term complications. Aims:: We conducted an internal audit of the short-to-medium term safety and absence of reported complications of the Altis® SIS in our medical centre (University Hospital of Leuven, Belgium). Secondary outcome was treatment efficacy, defined as no self-reported SUI symptoms. Methods:: A file review of all patients implanted with an Altis® sling at our institution between 2014 and May 2021 was performed. Baseline characteristics and outcomes were reported with the use of descriptive statistics. Results:: 212 women were included in our safety analysis, 192 women in the efficacy analysis. The safety analysis showed 74 complications of any kind. Mesh exposure occurred in 16 women (7.5%) after a mean period of 15 months. Eleven of them (5.2%) underwent excision of the exposed mesh. Arterial haemorrhage requiring embolization, and mesh infection, both occurred once. Dyspareunia for the patient (3.3%) or her partner (1.4%) was encountered in nine cases. Four cases were linked to mesh exposure, of which three underwent partial sling excision. De novo urgency (5.7%) and urge incontinence (7.3%) were reported in 25 women (13%) and were managed with anticholinergic drugs. Regarding efficacy outcomes, 161 women (83.8%) reported no residual urine loss at the first post-operative consultation. Thirteen women (6.7%) had persistent SUI. Eight women (4.2%) underwent reintervention receiving a second sling. Conclusion:: We can conclude that the short-to-medium term results in our centre align with those reported in existing literature.